2010
DOI: 10.1175/2009jhm1173.1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Land–Atmosphere Interaction from a Regional Climate Model Simulation over West Africa

Abstract: Land-atmosphere interaction at climatological time scales in a large area that includes the West African Sahel has been explicitly explored in a regional climate model (RegCM) simulation using a range of diagnostics. First, areas and seasons of strong land-atmosphere interaction were diagnosed from the requirement of a combined significant correlation between soil moisture, evaporation, and the recycling ratio. The northern edge of the West African monsoon area during June-August (JJA) and an area just north o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 36 publications
1
25
1
1
Order By: Relevance
“…Our results disagree somewhat with those of Van den Hurk and van Meijgaard (2010), who showed a strong sensitivity of the regional recycling ratio to soil moisture anomaly in, for example, JJA; in effect, they show a significant impact of soil moisture on precipitation later in the monsoon season, whereas we show almost none during this period. A study of their Sahelian soil moistures (their Fig.…”
Section: Summary and Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results disagree somewhat with those of Van den Hurk and van Meijgaard (2010), who showed a strong sensitivity of the regional recycling ratio to soil moisture anomaly in, for example, JJA; in effect, they show a significant impact of soil moisture on precipitation later in the monsoon season, whereas we show almost none during this period. A study of their Sahelian soil moistures (their Fig.…”
Section: Summary and Discussioncontrasting
confidence: 99%
“…4(a). This result supports those of Dirmeyer et al (2009) and Van den Hurk and van Meijgaard (2010), who found a high correlation between soil moisture and evaporation in MAM over the Western Fig. 4(b) are probably too small to have a significant impact on Ω P (R) -Ω P (W ) for two reasons: (a) σ E is itself small, implying a weak evaporation signal, and (b) the evaporation signal that does exist is not strongly similar amongst the members of the R ensemble.…”
Section: Role Of the Evaporation Signalsupporting
confidence: 91%
See 1 more Smart Citation
“…Perhaps the most important result of the use of regional models to study land surface processes is the uniform consensus that interactive land surface schemes improve the performance of climate models [216,[265][266][267]. They improve the simulation of hydrological processes, circulation features, and enhance predictive capacity.…”
Section: Land Surface Processes In Regional Modelsmentioning
confidence: 99%
“…On land, soil moisture is one of the few variables depicting the storage of water and heat that can be released several months later, as vegetation cover and snow do [5][6][7]. Even though the total energy represented by soil moisture is not comparable to that of the sea surface temperature, it could still constitute the turning point in studies on land-atmosphere interaction, seasonal climate forecasting and numerical simulations [8][9][10]. Soil moisture is also an indicator for drought and flood events, which are key factors in agriculture, hydrology, and ecology, among others.…”
Section: Motivationmentioning
confidence: 99%